Biochemical Properties of Myofibrillar Protein and Gel Characteristics of Surimi from Rohu (Labeo rohita) as Affected by Frozen Storage - Sakamut, Phatthira; Morioka, Katsuji; Sompongse, Warangkana (Science & Technology Asia, 2024)
The effects of frozen storage at -18ºC on the biochemical properties of myofibrillar protein (MF) extracted from rohu (Labeo rohita) surimi, and the gel characteristics of surimi were investigated. Biochemical changes were determined by the Ca2+-ATPase activity, total and reactive sulfhydryl (SH) content, and SDS-PAGE patterns. The gel properties were determined by gel strength, water holding capacity (WHC), whiteness, and from observations of the SDS-PAGE patterns and microstructure. Extended frozen storage was found to affect myosin. This was reflected in Ca2+-ATPase activity, reactive SH content, and myosin heavy chain intensity, which also decreased as the storage period was extended. This was confirmed by the decreasing of gel strength and WHC, the degradation of myosin heavy chain, and the formation of large protein clusters. The whiteness increased as the frozen storage time increased. This suggested that extended storage at -18ºC caused myosin denaturation, which in turn lead to a change of gel properties.